2015
DOI: 10.1098/rspb.2015.2230
|View full text |Cite
|
Sign up to set email alerts
|

Local effects drive heterozygosity–fitness correlations in an outcrossing long-lived tree

Abstract: Heterozygosity-fitness correlations (HFCs) have been used to understand the complex interactions between inbreeding, genetic diversity and evolution. Although frequently reported for decades, evidence for HFCs was often based on underpowered studies or inappropriate methods, and hence their underlying mechanisms are still under debate. Here, we used 6100 genome-wide single nucleotide polymorphisms (SNPs) to test for general and local effect HFCs in maritime pine (Pinus pinaster Ait.), an iconic Mediterranean f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 71 publications
(158 reference statements)
2
16
1
Order By: Relevance
“…These parameters are comparable to that reported in other organisms including trees (Rodríguez‐Quilón et al . ) and mammals (Annavi et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…These parameters are comparable to that reported in other organisms including trees (Rodríguez‐Quilón et al . ) and mammals (Annavi et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…With the widespread use of microsatellite markers for HFC studies, this discussion has focussed on the relative roles of ‘general’ and ‘local’ effects (e.g. Hansson & Westerberg, ; Rodriguez‐Quilon et al ., ), and the associated question of the link between marker‐based heterozygosity and inbreeding coefficients (e.g. Balloux et al ., ; Berenos et al ., ; Nietlisbach et al ., ), although these models are not mutually exclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the high levels of genetic diversity found in our study, we must be cautious when interpreting the intrinsic value of this remnant forest stand (Hedrick 1999). First, genetic diversity as estimated here only refers to neutral genetic diversity and not to variation associated with quantitative traits with adaptive value, and recent studies have shown little correlation between these two measures of diversity (e.g., Rodríguez-Quilón et al 2015). Second, high genetic diversity is accompanied by high levels of inbreeding and differentiated genetic clusters, which also calls for caution in the use of this stand as seed source (Ellstrand and Elam 1993;Charlesworth 2003).…”
Section: Discussionmentioning
confidence: 82%
“…In long-lived tree species, changes in effective population size, defined as the average number of individuals that contribute offspring to the next generation (Ridley 2003), may be slow and difficult to detect. Moreover, the fact that genetic processes operate in time units of generations may introduce important time lags in the response of forest trees to landscape change, including fragmentation (Wagner and Fortin 2013).…”
Section: Introductionmentioning
confidence: 99%